An overview of the potential therapeutic applications of essential oils - Nasser Aljaafari, Mariam; AlAli, Asma Obaid; Baqais, Laila; Alqubaisy, Maream; AlAli, Mudhi; Molouki, Aidin; Abdullah, Janna Ong; Abushelaibi, Aisha; Lai, Kok-Song; Lim, Swee Hua Erin (Multidisciplinary Digital Publishing Institute, 2021)
The emergence of antimicrobial resistance (AMR) has urged researchers to explore therapeutic alternatives, one of which includes the use of natural plant products such as essential oils (EO). In fact, EO obtained from clove, oregano, thymus, cinnamon bark, rosemary, eucalyptus, and lavender have been shown to present significant inhibitory effects on bacteria, fungi, and viruses; many studies have been done to measure EO efficacy against microorganisms. The strategy of combinatory effects via conventional and non-conventional methods revealed that the combined effects of EO-EO or EO-antibiotic exhibit enhanced efficacy. This paper aims to review the antimicrobial effects of EO, modes of EO action (membrane disruption, efflux inhibition, increase membrane permeability, and decrease in intracellular ATP), and their compounds' potential as effective agents against bacteria, fungi, and viruses. It is hoped that the integration of EO applications in this work can be used to consider EO for future clinical applications.